Epidemiology, Drug Susceptibility, and Clinical Risk Factors in Patients With Invasive Aspergillosis - Wang, Yuerong; Zhang, Luwen; Zhou, Longrong; Zhang, Min; Xu, Yuanhong (Frontiers in Public Health, 2022)
Background: To investigate the Aspergillus species distribution, antifungal sensitivities, clinical characteristics and risk factors of patients with invasive aspergillosis (IA) in a tertiary teaching hospital of Anhui Province. Methods: In the present study, 156 Aspergillus isolates were collected from patients admitted to a 2,800-bed comprehensive hospital between January 2019 and April 2021. The epidemiology of Aspergillus species was well examined, and its antifungal susceptibility was specifically measured by microbroth dilution method. The risk factors of patients with IA were documented and analyzed intensively. In addition, gene sequencing was employed to determine gene mutations of cyp51A associated with azole resistance among Aspergillus fumigatus. Results: The Aspergillus species distribution was dominated by A. fumigatus (56.41%), A. flavus (20.51%) and A. niger (15.38%) locally. In particular, all Aspergillus species showed very low minimum inhibitory concentrations (MICs, ≤ 0.50 μg/mL) for azoles and echinocandins, and slightly high MICs (1.66~2.91 μg/mL) for amphotericin B, but exceptionally high MICs (> 64.00 μg/mL) for flucytosine. Azole-resistant rate of Aspergillus species in this local region reached up to 5.79%. Correlation analyses of multiple antifungals indicate a significant MIC relevance between isavuconazole and voriconazole (Pearson correlation coefficient was 0.81, P < 0.0001). The clinical risk factors for IA patients were found primarily to be pulmonary diseases (P = 0.007) and patient age (P < 0.001). Notably, three mutant loci (TR46/Y121F/T289A) of cyp51A gene were identified in azole-resistant A. fumigatus. Conclusions: The Aspergillus species emerged increasingly, of which A. fumigatus and A. flavus remained the main pathogens for invasive Aspergillus infections in the local region. The vast majority of Aspergillus species exhibited good susceptibility to all the antifungals, except flucytosine. The local occurrence of azole-resistant Aspergillus species grew gradually and need monitor in time. Pulmonary diseases and age were likely considered as highly associated risk factors for IA. To our knowledge, the clinically isolated azole-resistant A. fumigatus with TR46/Y121F/T289A mutations identified here were rarely reported in the area of China.